CONSTRUCTED INTERACTIVE ANIMATION AS A MEDIA TO MEASURE STUDENTS' COLLABORATIVE PROBLEM SOLVING SKILLS AND IMPROVE STUDENTS' UNDERSTANDING IN LEARNING EARTHQUAKE - Anindi, Dinda Delima (2016)
This research aimed to investigate the improvement of students' understanding in earthquake topic and measure students' collaborative problem solving skills through the constructed interactive animation. The research was done in one of Public Junior High School in Bandung Indonesia, as it took the participant of 39 samples in 8th grade of Junior High School students. The method which is used in this research was mixed method with one group pre-test and post-test design. Based on quantitative analysis, students' understanding was improved from pre-test with the gain value of 0.30 which is categorized as low, yet the improvement between pre-test and post-test scores was significant of 0.00. Those are able to prove that interactive animation could improve students' understanding. In addition, this paper provides the result of observation of students' collaborative problem solving skills in every elements that students were already been really good at (C1) Communicating with team members about the actions performed, as the students were already used to collaborative learning by working as a group. Without ruling out the result of this research, it will be better to have the investigation on students' CPS skills improvement using interactive multimedia.